On Estimates of Non-Increasing Rearrangement of Generalized Fractional Maximal Function - Bokayev, Nurzhan; Abek, Azhar; Gogatishvili, Amiran (Eurasian Mathematical Journal, 2023)
We give a sharp pointwise estimate of the non-increasing rearrangement of the generalized fractional maximal function \((M_{Φ}f)(x)\) via an expression involving the non-increasing rearrangement of \(f\). It is shown that the obtained estimate is more sharp than the inequality which follows from the estimate for the generalized Riesz potential.